Association between geographical altitude and incidence of wild rabies in cattle in the Apurimac region (2004-2015) - Pineda Serruto, Martín Equicio (2021)
Latin American cattle farming is affected by the wild rabies virus whose vector is Desmodus rotundus. In 2014, Apurímac, Peru registered the highest number of cases (n=75) The objective of the study was to determine the association between calendar time and wild bovine rabies outbreaks at different geographical altitudes in the Apurímac valley, between the years 2004 and 2015. Data from the SIGSA-SENASA (Integrated Animal Health Management System of the National Agrarian Health Service) on geographical altitude (m) and date of suspected outbreaks of wild rabies confirmed by direct immunofluorescence were analysed. The data were analysed using the Chi square test, t-Student, Spearman’s rho correlation and Poisson’s generalized linear models (GLM). In total, 525 suspected outbreaks were analysed (altitude range: 999-4586 m), finding differences for the number of outbreaks according to altitudes: high, medium and low (p<0.05). No correlation was found between outbreak altitude and calendar time or association between geographical altitude of the wild rabies outbreak with calendar time adjusted by seasonality and rearing system. It is concluded that there was an association between the number of cases of wild rabies and geographic altitude (p<0.05), without association with calendar time. Likewise, a negative association was observed with the average minimum temperature (p<0.01).